Molecular Biology and Pathogenesis of Peste des Petits Ruminants Virus - Munir, Muhammad; Zohari, Siamak; Berg, Mikael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Peste de Petits Ruminants (PPR) is a highly contagious viral disease of domestic and wild small ruminants that can significantly affect economies. The authors are experts in the field and provide an up-to-date and comprehensive review covering all aspects of the disease. The book is divided into seven chapters highlighting genome organization, virus replication and the determinants of virulence, pathophysiology and clinical disease, immunology and immunopathogenesis, epidemiology, diagnostic assays and vaccines, and the challenges concerning global eradication. It is an invaluable reference work, presenting the latest information for virologists, microbiologists, immunologists, veterinarians, and scientists working in PPR research.
Genome Organization of Peste des Petits Ruminants Virus -- Replication and Virulence Determinants of Peste des Petits Ruminants Virus -- Pathophysiology and Clinical Assessment of Peste des Petits Ruminants -- Immunology and Immunopathogenesis of Peste des Petits Ruminants Virus -- Epidemiology and Distribution of Peste des Petits Ruminants -- Current Advances in Molecular Diagnosis and Vaccines for Peste des Petits Ruminants -- Poverty Alleviation and Global Eradication of Peste des Petits Ruminants.
Keywords: Medicine; Immunology; Medical virology; Veterinary medicine; Wildlife management; Biomedicine; Virology; Immunology; Fish & Wildlife Biology & Management; Veterinary Medicine